Determinants of factors influencing the utilization of Covid-19 vaccination services at sigli public health center, Pidie Regency, Aceh, Indonesia - Fauza, Riska; Hidayat, Melania; Zahara, Meutia; Radhiah, Radhiah; Abdullah, Asnawi (Science Midwifery, 2024)
This study aims to identify the factors influencing people's utilization of vaccination services at the Sigli City Health Center. This research employed an analytical observational design with a cross-sectional approach. Independent variables included age, occupation, education, knowledge, accessibility, family support, perception, and immunization history, while the dependent variable was the utilization of the Covid-19 vaccine service. The study was conducted in November, with a sample size of 371 respondents selected using random sampling techniques based on the Slovin formula. Data were collected through questionnaires distributed to the respondents. The research findings revealed that approximately 78.71% of the population utilized the vaccine service, while 21.29% did not. Bivariate analysis indicated that out of the eight variables examined, five variables had a significant relationship with the utilization of the Covid-19 vaccine service, namely occupation, knowledge, accessibility, family support, and perception, each with a p-value of 0.000. Multivariate analysis further confirmed that knowledge was the most dominant factor, with a p-value of 0.000 and an Odds Ratio of 23.3 (95% CI = 63.5-85.9). Thus, a lack of knowledge was found to be a significant factor influencing the utilization of the Covid-19 vaccine service.